The consistencies and inconsistencies between distal cholangiocarcinoma and pancreatic ductal adenocarcinoma: A systematic review and meta-analysis - Lv, Tian-Run; Wang, Ju-Mei; Ma, Wen-Jie; Hu, Ya-Fei; Dai, Yu-Shi; Jin, Yan-Wen; Li, Fu-Yu (Frontiers in Oncology, 2022)
Abstract Objective: To evaluate the consistencies and inconsistencies between distal cholangiocarcinoma (DCCA ) and pancreatic ductal carcinoma (PDCA) regarding their biological features and long-term prognosis. Methods: PubMed, the Cochrane Library and EMBASE were searched to find comparative studies between DCCA and PDCA. RevMan5.3 and Stata 13.0 software were used for the statistical analyses. Results: 11 studies with 4698 patients with DCCA and 100629 patients with PDCA were identified. Pooled results indicated that patient with DCCA shared a significantly higher rate of preoperative jaundice (P=0.0003). Lymphatic metastasis (P<0.00001), vascular invasion (P<0.0001) and peri-neural invasion (P=0.005) were more frequently detected in patients with PDCA. After curative PD, a significantly higher R0 rate (P<0.0001) and a significantly smaller tumor size (P<0.00001) were detected in patients with DCCA. Patients with DCCA shared a more favorable OS (P<0.00001) as well as DFS (P=0.005) than patients with DCCA. However, postoperative morbidities (P=0.02), especially POPF (P<0.00001), were more frequently occurred in DCCA. Conclusion: DCCA shared a more favorable tumor pathological features and long-term prognosis than PDCA. An early diagnosis was more frequently occurred in patients with DCCA. However, postoperative complications, especially POPF, were more frequently observed in patients with DCCA.